IMPROVING STUDENTS’ ABILITY IN READING COMPREHENSION OF NARRATIVE TEXT THROUGH GROUP WORK ACTIVITY - Pratama, Denny; Bunau, Eusabinus; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak:Penelitianinibertujuanuntukmeningkatkankemampuansiswadalammemahamiteksnaratif. Penelitianinidilakukanpadasiswakelas VIII SMP Negeri 14 Pontianak tahunakademik 2011/2012.Metode yang digunakandalampenelitianiniadalahpenelitiantindakankelas.Subjek penelitianiniterdiriatas 30 siswadarikelas VIIIC. Dalam penelitian ini peneliti bertindak sebagai guru.Data penelitiandidapatkandenganmenggunakanteknikpenilaiandanobservasidandianalisamenggunakanceklisobservasi, catatanlapangandannilai rata-rata siswa.Ada tigasiklusdalampenelitianini.Hasilpenelitianmenunjukkanbahwanilai rata-rata siswapadasikluspertamayaitu 60,7, sikluskeduayaitu 63,3, danpadasiklusketigayaitu 68,1. Nilaiinimenunjukkanbahwasiswatelahberhasilmencapaikriteriaketuntasan minimum (KKM) di sekolahiniyaitu 65.Padasikluspertamasiswasudahmampumenentukan ide utama.Teknikinimembantusiswadalammemahamiapa yang dimaksudolehpenulisdanbisamengambilkesimpulandariteksnaratif yang diberikan. Kata Kunci:PemahamanBacaan, Kerja Kelompok, TeksNaratif. Abstract: The aim of this research isto improvestudents’ reading comprehension onnarrative text. This research was conducted to eighth year students of SMP Negeri 14 Pontianak in academic year 2011/2012.The method of this research is classroom action researchThesubjectwas taken fromclass VIII C that consistsed of 30 students.The researcher acted as the teacher during the research period. The data were collected by using measurement and observation techniques and analyzed by describing the observation checklist, field note, and the students’ score. The researcher conducted the research in three cycles. The research findings show that the mean score of students’ reading comprehension test in the first cycle is 60.7, the second cycle is 63.3, and in the third cycle is68.1It means that students successfully pass the KriteriaKetuntasan Minimum (KKM) in this school that is65.This technique helped the students in understanding what the author meant and in drawing the conclusion from the narrative text given to them. Keywords: ReadingComprehension, GroupWork, NarrativeText